A Survey on Awareness on Pregnancy Related Complications and Associated Factors - Ankita Dongare,; Tejas Deshmukh,; Bhavika Bahekar,; Akanksha Patil,; Prachi Shivankar,; Dr. Nitin Indurwade, (Asian Journal of Pharmaceutical Research and Development, 2026)
Pregnancy related complications are a major health concern in our country. Awareness of these complication is essential for early detection of complication and prevention of maternal mortality. The purpose of this study was to analyze the awareness regarding the pregnancy related complications and associated factors in pregnant and parous women. It was questionnaire based survey conducted in pregnant and parous women contains both open-ended and close ended questions covering the knowledge of complication like, anemia, gestational hypertension, gestational diabetes, pre-eclampsia, ectopic pregnancy, preterm birth. Finding of the survey indicates that the women had general awareness about complications but more awareness is still needed. high educational status, regular antenatal care attendance and exposure to health information can reduce the incidence of complications. the survey asses the role of ANC in prevention of complications and reduce the maternal health risk.